Effects of the COVID-19 Health Crisis on Sports Practice, Life Quality, and Emotional Status in Spanish High-Performance Athletes - Conde, Elena; Martínez-Aranda, Luis Manuel; Sanz, Gema; López de Subijana, Cristina; Sánchez-Pato, Antonio; Díaz-Aroca, Álvaro; Leiva-Arcas, Alejandro; García-Roca, Juan Alfonso; Ramis, Yago; Torregrossa, Miquel (Frontiers in Psychology, 2021)
Spain is one of the many countries highly affected by the COVID-19 crisis, establishing very restrictive measures with a complete lockdown for more than 3 months. This situation forced the complete closure of sport practice and national or international competitions, leading to a negative impact on high-performance athletes’ physical and psychological health. Therefore, the objectives of this study were: (a) to determine the effects of the COVID-19 health crisis on Spanish high-performance athletes in terms of sports practice, life quality and emotional state; (b) to identify the profile with the greatest difficulties during and after the lockdown. A sample of 130 high-performance athletes aged between 18 and 34 years (67 women and 63 men) participated in this study (83.1% achieved a medal in National-International elite competitions; 86.9% were considered student-athletes). Measures included socio-demographic data through a 5-dimensions ad hoc survey; physical activity and exercise using an adapted version from the International Physical Activity Questionnaire (IPAQ); health status and limitations using an adapted version of SF-12 Health Questionnaire; Perceived stress (Short-PSS); and Mood States (29-item POMS). All participants have shown a significant decrease pre-post-lockdown in both health and performance perception, especially in women, individual athletes, medallists and student-athletes. Strong limitations of training, attention, and motivation as well as a moderate negative emotional state during lockdown were reported, in women, individual athletes, medallists and student-athletes. Even with an improved emotional state and energy level in the post- lockdown period, moderate-to-high stress scores were reported by women and medallists. Our findings highlight the importance of paying attention to the physical and psychological health of elite athletes on three profiles: team athletes (due to social distance), student-athletes (dual-career issues) and women athletes (prevalence of implicit gender inequalities in sport).